Formalising and repairing semantic networks of ontologies with linear temporal logics. (2016) - Kolli, Manel
In this study, we exploit the semantic network mechanisms to deal with the alignment of a set of ontologies. We formally define the interoperability among the networked ontologies and we show how they can be modelled as an ontology network with the Linear Temporal Logics (LTLs). These logics consist of expressing properties over a single sequence of states. This view is suitable for the reasoning of semantic networks of ontologies where we assume a sequence of alignments. The formalisation enables to handle the potential incoherencies caused by aligning different ontologies in the semantic web. In our case, LTL operators play an important role, specially, in the process of debugging the set of incoherent mappings and providing relevant definitions for repairing these incoherent mappings in the semantic network of ontologies.